BEBERAPA ASPEK PENGELOLAAN CAGAR ALAM RAWA DANAU SEBAGAI SUMBER AIR BAKU - Priyanto, Budhi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Economically, Rawa Danau is important fresh water source for cities ofCilegon and Serang and industrial estates in the area. Ecologically, RawaDanau is the last and the only mountainous freshwater swamp still exists inJava island. In the last decade there are several studies that recommendincreasing the capacity of Rawa Danau as water storage. Recently, theMaster Plan of Rawa Danau has been published by the Province of BantenPlanning Agency. It is concluded that increasing the water level in RawaDanau by 2 meters would satisfies the 2010 projected water demand inSerang and Cilegon. We belief that the action could endanger theexistence of both the swamp forest and the rice field in the vicinity. In thispaper we describe an alternative action that could increase the waterstorage capacity of Rawa Danau whilst the ecological function of theswamp could be preserved as well.